Pola Komunikasi Organisasi Aisyiyah Kabupaten Karanganyar Di Era Modernisasi - Lestari, Ayu Ria; Ikhwan, Muhammad Isnan Nur; Syahiddinillah, Fajri; Swarnawati, Aminah (CV. ITTC INDONESIA, 2025)
Effective communication patterns are key in running complex organizations like 'Aisyiyah. Understanding the communication model used can provide insights to enhance communication effectiveness in religious and social organizations in Karanganyar and identify the factors influencing it. The communication pattern in this organization utilizes an all-channel communication model, which operates without hierarchical barriers. The research method used is qualitative with a case study approach, through in-depth interviews and observations of the active organization leaders. The research results show that the communication pattern implemented in 'Aisyiyah Karanganyar has built strong interpersonal relationships, facilitated collaboration, and created an inclusive and empowering work climate. The communication conducted is informative but also persuasive and motivating, bringing significant positive impacts to the community served. The open and transparent communication pattern allows quick and adaptive responses to changes and strengthens members' solidarity and a sense of belonging.